Guardians of research: negotiating the strata of gatekeepers in research with vulnerable participants. Issue 1 (2nd January 2019) - Kay, Lynda
ABSTRACT: Gatekeepers are an integral part of an ethical process of seeking authorisation for research. The number of gatekeepers, and the negotiations between researchers and gatekeepers, become more complex for research which includes children and young people (CYP) and other vulnerable groups. Ethical researchers and gatekeepers share a desire to protect CYP from harm. This paper examines the multifaceted nature of gatekeepers and the positive and negative influences upon their decision-making and thus potentially upon the shaping of a research project. The traditional view of the gatekeeper, as benevolent protector, has been challenged within literature. Indeed, gatekeepers are sometimes presented as being predisposed to take an antagonistic stance towards research proposals, owing to a heightened anxiety regarding risks of harm for CYP. Further influences upon the gatekeeper's decision-making include their perceptions of the construct of childhood and of CYP's competences with understanding and articulating their thoughts, feeling and experiences, contextual issues and obligations set out within policy or legislation. This is problematic for researchers endeavouring to plan proactively for seeking permissions from gatekeepers to involve CYP within research projects.  This paper offers a novel contribution to these debates with a model of the strata of gatekeepers, designed to support researchers with those proactive preparations. This paper focuses on the educational context, but nevertheless contributes to the debates across wider fields of study, working to mitigate vulnerable participants becoming marginalised on topics which are salient to them.